2023
DOI: 10.21203/rs.3.rs-3765606/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flow regime identification of air-water two-phase counter-current flow in vertical annulus and eccentricity effect analysis:a machine learning approach

Feng Cao,
Ruirong Dang,
Bo Dang
et al.

Abstract: Gas-liquid two-phase counter-current flow has been involved in many industrial fields, due to the existence of the inner pipe and the variation of the eccentricity of the inner and outer pipes, the flow regimes are difficult to be visual identification. To solve this problem, a vertical annulus with adjustable eccentricity was designed. Experiments were carried out under different combination of gas-liquid flowrate and eccentricity. The feature vector was formed by PDF and principal components of PSD of two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The 0.27-2.80 Hz frequency band reaches a maximum at V sg = 0.994 m s −1 , which may be related to flow regime changes. In another paper by the author focusing on flow regime identification [36], the issue of flow regime transformation under the same column configuration was studied. The results showed that under the counter-current flow conditions of gas-liquid twophase, the flow regime transformation is mainly influenced by gas superficial velocity, with the gas superficial velocity for the transformation from slug flow to churn flow being approximately V sg = 1.0 m s −1 .…”
Section: Analysis Of the Impact Of Gas-liquid Flow Velocity And Eccen...mentioning
confidence: 99%
See 1 more Smart Citation
“…The 0.27-2.80 Hz frequency band reaches a maximum at V sg = 0.994 m s −1 , which may be related to flow regime changes. In another paper by the author focusing on flow regime identification [36], the issue of flow regime transformation under the same column configuration was studied. The results showed that under the counter-current flow conditions of gas-liquid twophase, the flow regime transformation is mainly influenced by gas superficial velocity, with the gas superficial velocity for the transformation from slug flow to churn flow being approximately V sg = 1.0 m s −1 .…”
Section: Analysis Of the Impact Of Gas-liquid Flow Velocity And Eccen...mentioning
confidence: 99%
“…According to the research in another paper by the author [36], which focuses on flow pattern identification under the same column configuration, the flow patterns involved in this experiment include bubble flow, slug flow, and churn flow. Due to equipment limitations, annular flow cannot be generated.…”
Section: Comparison With Similar Studiesmentioning
confidence: 99%